Strengthening Qur'an-Based Political Education for Generation Z - Hazrul Azwan; Muhammad Zulfikar Ramadan NPT; Maisarah Khairani Putri; Syafira Aura; M. Rizal Aditya Berutu (Yayasan Bayt Shufiya Nusantara, 2026)
This study examines the contribution of Qur'an-based democratic education to strengthening the political awareness of Generation Z. It employs a qualitative library research design with a descriptive-analytical approach using content analysis. The data were drawn from scholarly journal articles, academic books, Qur'anic exegesis (tafsir), and other relevant academic documents, which were analyzed thematically to identify the conceptual relationship between democratic education, Qur'anic values, and political awareness. The findings indicate that Qur'an-based democratic education enhances Generation Z's political awareness by internalizing the values of justice, consultation (shūrā), responsibility, honesty, and public welfare (maṣlaḥah) within democratic life. The study further reveals that integrating humanistic and religious approaches fosters critical, moderate, and responsible attitudes toward contemporary political issues. Therefore, Qur'an-based democratic education provides a relevant conceptual framework for improving political literacy while cultivating an ethical democratic culture among Generation Z.